Wytyczne dotyczące postępowania w przypadku niedowidzenia u dzieci - Loba, Piotr; Gotz-Więckowska, Anna; Hautz, Wojciech; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2022)
Amblyopia is the most common cause of decreased visual acuity in children. Among adults, it shows itself to be the major cause of unilateral visual impairment. Amblyopia compromises the quality of life and has an adverse impact on the range of available occupational opportunities. The Section of Pediatric Ophthalmology and Strabismus Treatment of the Polish Ophthalmological Society presents guidelines and recommendations on the basic principles of amblyopia management in children.